Planificación Estratégica para el Gobierno Autónomo Descentralizado del Cantón Palanda de la Provincia de Zamora Chinchipe para el Período 2016-2019 - Cabrera Cueva, Gabriela Elizabeth (2017)
Decentralized Autonomous Government of Palanda Canton is a legal entity of public law with political, administrative and financial autonomy, is composed of the functions of citizen participation; legislation and enforcement; and executive provided for in the COOTAD, for the exercise of the functions and responsibilities assigned to it. The Special Titling work has been developed with the purpose of carrying out a Strategic Planning for the Decentralized Autonomous Government of Canton Palanda of the Province of Zamora Chinchipe for the Period 2016-2019, as an information tool, decision and control at the level of performance of their functions, which allows to establish, determine, recognize the relevant institutional needs and quantify them; was executed feasibly with the support and implementation of a methodology consistent with the objectives set for it a conceptual approach on strategic planning considering its scope and requirements was conducted, which allow introduce to the implementation of the proposal starting with obtaining information by applying a structured interview addressed to the Mayor, surveys for staff and residents of the canton in order to comply with the objectives is to develop a SWOT matrix in order to determine the strengths, weaknesses, opportunities and threats, They exist within and outside the institution and thus help improve the situation of the GAD and 5 so they can make decisions consistent with the objectives and policies formulated and subsequently the strategic objectives to help optimize time and resources were designed to meet its goals and activities. Its formal structure presents an introduction, which focuses on the importance of the subject, the benefit can be provided with work and it is structured the same, in the literature review are focused concepts that will help the interpretation of the proposed proposal, then materials and methods used in preparing the thesis explains. Finally, conclusions and recommendations among the most important are written : The training of human resources is not met fully , a situation which is produced by the absence of annual plans that support the incorporation, designed to complement professional elements and working institutional budget in their competition , just as it is concluded that the system of information and communication GAD Canton due to ignorance of the importance of informing citizens of the action of its constituents also established in the law, a situation that encourages ignorance both internal and external stakeholders of the institution; so modestly it suggested considering the proposal of strategic planning from 2016 to 2019, To promote management and institutional management.